The First Teachers of Jewish Religion in State Secondary Schools in the Kingdom of Poland - the Alumni of Vilnius Rabbinic School - Kula, Ewa (Respectus Philologicus, 2003)
Possibilities for employing the teachers of Jewish religion in State secondary schools in the Kingdom of Poland occurred after the proclamation in June 1862 ukases prepared by Aleksander Wielopolski. Such possibilities were given both by the repealing restrictions ukase of tolerance of Jews, and the ukase reforming the educational system as well. After the failure of the January Insurrection, the Russian Government intended to unify the Polish and Russian education setting up with Jugenheim’s ukases (30.08/11.09.1864) and January acts (1866) schools for the Russian, Lithuanian, German and Jewish populations. These schools were created in order to secure the children of mentioned above national minorities from polonization by establishing Russian as an official language. The teachers of Jewish religion, mainly the alumni of Vilnius rabbinic school, were employed in these institutions since 1865. The first teachers in men’s state secondary schools in the Kingdom of Poland were: Aleksander Donchin, Mojzesz Goldsztein, Salomon Zeligman, Izrael Alapin, Szymon Chodak, Bernard Segal, Abraham Solonowicz, Abraham Papiema. Three of them, B. Segal, A. Solonowicz and A. Papiema, were the authors of Jewish religion handbooks, translations from Hebrew to Russian, and the papers on Jewish problems published in the columns of periodicals. Mentioned in the paper alumni of Vilnius rabbinic school did not have any pedagogical training, so they worked out their own methods of teaching. Their work and activity was followed by graduates of established in 1873 in Vilnius pedagogical institute of four years’ course of studying.